THE EFFECT OF HUMAN RESOURCES COMPETENCE, GOAL ORIENTATION, BUDGET USE, AND MONITORING AND EVALUATION ON PERFORMANCE-BASED BUDGET MANAGEMENT SYSTEMS IN MANAGEMENT AGENCY REGIONAL FINANCE OF EAST LUWU REGENCY - Adri E.; Paulus Tangke; Yakobus K. Bangun (Fakultas Ekonomi dan Bisnis Universitas Atma Jaya Makassar, 2022)
This study aims to examine the effect of HR competence, goal orientation, budget use, as well as monitoring and evaluation of the performance-based budget management system at the Regional Financial Management Agency of East Luwu Regency. To achieve this goal, data collection techniques were used through questionnaires, with data analysis techniques using multiple linear regression analysis, validity and reliability tests, classical assumption tests and hypothesis testing. The results of the research conducted found that HR competence had an effect on the performance-based budget management system. Goal orientation affects the performance-based budget management system. The use of the budget affects the performance-based budget management system, and monitoring and evaluation has a positive and significant effect on the performance-based budget management system at the Regional Financial Management Agency in East Luwu Regency, while the results of regression testing show that the dominant variable affects the performance-based budget management system. on the Regional Financial Management Agency in East Luwu Regency is the use of the budget.